(untitled) - Suksri, Naengnoi (Thailand, 1998)
Art and architecture of Grand Palace, Bangkok, Thailand; includes a chapter on royal ceremonies.
Keywords: Bangkok (Thailand),Bangkok (Thái Lan); Buildings, structures, etc.,Tòa nhà, cấu trúc, v.v.